MERIDIAN ACUPUNCTURE IN STROKE REHABILITATION: A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i2.100 - Deny Prasetyanto; Sri Yona (International Journal of Nursing and Health Services (IJNHS), 2019)
Abstract Rehabilitation therapy has an important role in restoring bodily functions comprehensively due to stroke which aims to restore function so as to reduce disability. One therapy that nurses can do is to use acupuncture meridian points. Acupuncture is considered to play a leading role in the treatment of symptoms related to stroke. This literature review aims to analyze the benefits of the acupuncture points in stroke rehabilitation. The research method used by the author is a literature review using several databases namely Pubmed, Cochrane Library, EbscoHost, Proquest and Google Scholar from 2008 to 2018. An article that discusses rehabilitation of stroke patients using acupuncture meridian points is used as a medium of rehabilitation. The literature search results show that the rehabilitation of acupuncture meridian points provides the benefits of recovery of stroke symptoms such as hemiparese, dyspagia, dementia, and reduced volume and infarction including neurological deficits so as to improve the quality of life for stroke patients. Keywords: stroke, rehabilitation, quality of life, acupuncture, meridians